A Retrospective Analysis and Comparison of Prisoners and Community-Based Patients with COVID-19 Requiring Intensive Care During the First Phase of the Pandemic in West Texas. (August 2020) - Ali, Kiran; Rao, Sanjana; Berdine, Gilbert; Test, Victor; Nugent, Kenneth
Background: COVID-19 is a highly infectious disease which usually presents with respiratory symptoms. This virus is disseminated through respiratory droplets, and, therefore, individuals residing in close quarters are at a higher risk for the acquisition of infection. The prison population is at a significantly increased risk for infection. Methods: Prisoners from the Montford Correctional facility in Lubbock, Texas, hospitalized in the medical intensive care unit at University Medical Center between March 1, 2020 and May 15, 2020 were compared to community-based patients hospitalized in the same medical intensive care unit. Clinical information, laboratory results, radiographic results, management requirements, and outcomes were compared. Results: A total of 15 community-based patients with a mean age of 67.4 ± 15.5 years were compared to 5 prisoners with a mean age of 56.0 ± 9.0 years. All prisoners were men; 10 community-based patients were men. Prisoners presented with fever, dyspnea, and GI symptoms. The mean number of comorbidities in prisoners was 2.4 compared to 1.8 in community-based patients. Prisoners had significantly lower heart rates and respiratory rates at presentation than community-based patients. The mean length of stay in prisoners was 12.6 ± 8.9 days; the mean length of stay in community-based patients was 8.6 ± 6.5. The case fatality rate was 60% in both groups. Conclusions: Prisoners were younger than community-based patients but required longer lengths of stay and had the same mortality rate. This study provides a basis for comparisons with future studies which could involve new treatment options currently under study.